2007
DOI: 10.1902/jop.2007.060032
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Pain Associated With the Surgical Placement of Dental Implants

Abstract: Pain experienced by patients following the surgical placement of dental implants was generally mild and gradually decreased with time. Operator experience, female gender, surgical difficulty, and pain at earlier time-points were associated significantly with patient reports of pain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
123
4
3

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(153 citation statements)
references
References 25 publications
18
123
4
3
Order By: Relevance
“…Another concern is related to the time-interval of questionnaire assessment. Previous studies [11,12] demonstrated that the peak pain scores were at 24 h after surgery. However, since they did not measure the symptoms in short-term periods, the peak symptoms could be within the first 24 h. Indeed, another study that evaluated postoperative pain and inflammation showed that peak symptoms were observed at 6 h after surgery [3].…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Another concern is related to the time-interval of questionnaire assessment. Previous studies [11,12] demonstrated that the peak pain scores were at 24 h after surgery. However, since they did not measure the symptoms in short-term periods, the peak symptoms could be within the first 24 h. Indeed, another study that evaluated postoperative pain and inflammation showed that peak symptoms were observed at 6 h after surgery [3].…”
Section: Discussionmentioning
confidence: 94%
“…During the recruited period, a total of 33 subjects (male/ female: 11 treated as the final subjects. The total return rate of c-EMA survey was 90.6% (240/265).…”
Section: Resultsmentioning
confidence: 99%
“…In a series 41 patients (8) 131 dental implants were placed, observing peak pain at 6 hours after surgery in 41.5% of patients. Al-Khabbaz et al (4) observed that after 24 hours, 80.3% of patients had some pain, the majority of which was mild (69.7%); after one week 60.3% of patients still had some pain, whereas at 6 weeks 5.1% of patients had mild pain, and none of the patients had pain at 12 weeks. At 24 hours, pain was significantly related to the implants placed in women, implants placed by graduate students, and with the presence of pain during surgery.…”
Section: Postoperative Pain (Side Effects)mentioning
confidence: 99%
“…Most patients do not report pain during implant surgery, where pain is related to the number of implants placed (4) and anxiety (5). Several articles have studied pain and swelling secondary to procedures such as removal of impacted third molars (6), periapical surgery (7) and implant placement (4,8). A review by Greenstein et al (9) reported clinical recommendations for preventing and managing surgical complications associated with implant placement; complications causing pain were nerve injury, wound dehiscence, injury to an adjacent tooth, mandibular fracture and maxillary sinusitis.…”
Section: Introductionmentioning
confidence: 99%
“…Perception of pain varies among individuals because it is a multifaceted emotional and sensory experience that is associated and exaggerated with previous experience, expected stress, clinical situation and anxiety [7]- [9]. Fear of this pain represented by anxiety, is one of the most common factor related with dental fear, and 40% of the population has been reported to suffer from it [10]- [12].…”
Section: Introductionmentioning
confidence: 99%